Karakteristik Sensori dan Fisiko-Kimia Crackers dengan Penambahan Tepung Ikan Sepat Siam (Trichogaster pectoralis) - Dahlia Puspita Sari; Rodiana Nopianti; Ace Baehaki (Jurnal FishtecH, 2017)
Crackers are a type of biscuits produced through a fermentation process. They are crunchy, have a flat shape and a rather salty taste, and when broken, they show a multi-layered cross-section. A study on the effects of the addition of siamese gourami fish meal on the sensory and physicochemical characteristics of crackers was carried out at the laboratory of Fishery Technology. This research used a randomized block design with five treatments of different types of the concentration of siamese gourami fish meal, i.e. 0%, 5%, 10%, 20% and 30%. The observed parameters were sensory characteristics, physical characteristics (color and crispiness) and chemical characteristics (water content, ash content, protein content, fat content, and carbohydrate content). The results suggest that the addition of siamese gourami fish meal significantly affects the sensory characteristics (appearance, odor, color, texture and crispiness), as well as chemical characteristics (ash content, moisture content, protein content, fat content, and carbohydrate content). The best treatment found in this research was A2 (20 g fish meal : 180 g wheat starch).